Biotechnology and biopharmaceuticals : transforming proteins and genes into drugs - Ho, Rodney J. Y.; Gibaldi, Milo. (Hoboken, New Jersey : Wiley Blackwell, 2013)
Biotechnology and Biopharmaceuticals: Transforming Proteins and Genes into Drugs, Second Edition addresses the pivotal issues relating to translational science, including preclinical and clinical drug development, regulatory science, pharmaco-economics and cost-effectiveness considerations. The new edition also provides an update on new proteins and genetic medicines, the translational and integrated sciences that continue to fuel the innovations in medicine, as well as the new areas of therapeutic development including cancer vaccines, stem cell therapeutics, and cell-based therapies.
Introduction to biopharmaceuticals -- Distinctions of biologic versus small molecule platforms in drug development -- Financing biologic drug development -- Application of biotechnology in drug discovery and early development -- Large-scale production of recombinant proteins -- Clinical pharmacology, toxicology, and therapeutic dosage & response -- Clinical evaluation and regulatory approval & enforcement of biopharmaceuticals -- Pharmacoeconomics and drug pricing / Garrison -- Antibodies and derivatives -- Hematopoietic growth and coagulation factors -- Cytokines and interferons -- Hormones -- Enzymes -- Vaccines / Hu, Ho -- Other biopharmaceutical products -- Advances in personalized medicine : pharmacogenetics in drug therapy -- Gene and cell therapy -- Pharmacoeconomics, outcome, and health technology assessment research in drug development -- Summary and future prospects.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Pharmaceutical biotechnology; Biopharmaceutics; Chemistry, Pharmaceutical; Drug Design; Biopharmaceutics; Chemistry, Pharmaceutical; Drug design; Electronic books; Electronic books